Effect of Nursing Quality Management on the Nosocomial Infection Rate and Psychology State of Patients with Burn and Plastic Surgery - Xue WANG; Qi XU; Xu LIU; Aiqin LV (Tehran University of Medical Sciences, 2020)
Abstract Background: To explore the effect of nursing quality management on the nosocomial infection rate and Psychology State of patients with burn and plastic surgery. Methods: Overall, 92 patients with burn and plastic surgery admitted to Qilu Hospital, Jinan, China from Apr 2017 to Jul 2018 were selected, in which 46 cases were randomly selected as a control group for routine nursing management, and another 46 cases as a research group to strengthen nursing quality management. The incidence of nosocomial infection, nursing satisfaction and nurse-patient disputes were compared. MMAS-8 scale was used to compare the compliance of the two groups. SAS and SDS score were used to compare the psychological status. The recovery and discharge were compared. Results: The incidence of nosocomial infection in the study group was significantly lower than that in the control group (P<0.05). The total satisfaction rate of the study group was significantly higher than that of the control group (P<0.05). The incidence of nurses-patients disputes was significantly lower than that of the control group. The SAS and SDS score of the study group were significantly better than the control group (P<0.05). The healing time, blood circulation recovery time of skin wounds and discharge time in the study group were significantly better than those in the control group. Conclusion: Strengthening nursing quality management can effectively reduce the nosocomial infection rate of burn and plastic surgery. It helps to further accelerate the recovery of patients and make patients' psychological state better.